Myelin Damage in Normal Appearing White Matter Contributes to Impaired Cognitive Processing Speed in Multiple Sclerosis. Issue 2 (24th November 2019) - Abel, Shawna; Vavasour, Irene; Lee, Lisa Eunyoung; Johnson, Poljanka; Ackermans, Nathalie; Chan, Jillian; Dvorak, Adam; Schabas, Alice; Wiggermann, Vanessa; Tam, Roger; Kuan, Annie J.; Morrow, Sarah A.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Cognitive impairment is a core symptom in multiple sclerosis (MS). Damage to normal appearing white matter (NAWM) is likely involved. We sought to determine if greater myelin heterogeneity in NAWM is associated with decreased cognitive performance in MS. METHODS: A total of 27 participants with MS and 13 controls matched for age, sex, and education underwent myelin water imaging (MWI) from which the myelin water fraction (MWF) was calculated. Corpus callosum, superior longitudinal fasciculus, and cingulum were chosen as regions of interest (ROIs) a priori based on their involvement in MS‐related cognitive impairment. Cognitive performance was assessed using the Symbol Digit Modalities Test (SDMT). Pearson ́s product moment correlations were performed to assess relationships between cognitive performance and myelin heterogeneity (variance of MWF within an ROI). RESULTS: In MS, myelin heterogeneity in all three ROIs was significantly associated with performance on the SDMT. These correlations ranged from moderate ( r = −.561) to moderately strong ( r = −.654) and were highly significant ( P values ranged from .001 to .0002). Conversely, myelin heterogeneity was not associated with SDMT performance in controls in any ROI ( P > .108). CONCLUSION: Increased myelin heterogeneity in NAWM is associated with decreased cognitive processing speed performance in MS.